Evolving Paradigms in the Management of Multiple Myeloma: Novel Agents and Targeted Therapies. Issue 1 (December 2015) - Larsen, Jeremy; Kumar, Shaji
Abstract Multiple myeloma (MM) is a clonal plasma cell disorder defined by bone marrow infiltration and osteolytic bone lesions and is the second most common hematologic malignancy after non-Hodgkin lymphoma. The landscape of MM treatment was transformed at the dawn of the twenty-first century by the introduction of novel agents including proteasome inhibitors (bortezomib) and immunomodulatory drugs (thalidomide, lenalidomide), which have prolonged the survival of MM patients. The recently revised International Myeloma Working Group diagnostic criteria for MM added validated biomarkers (clonal bone marrow plasma cell ≥60%, involved:uninvolved serum free light chain ratio ≥100, or >1 focal lesion on magnetic resonance imaging) to identify near inevitable progression to symptomatic MM requiring therapy. In addition, the definition of myeloma-defining CRAB features (hypercalcemia, renal failure, anemia, and bone lesions) has been refined based on advances in imaging and laboratory techniques since the 2003 IMWG consensus. Despite expanded treatment options, MM remains an incurable disease. Drug resistance and clonal evolution remain problematic, and novel therapeutic agents are needed. New approaches to myeloma treatment include anti-CD38 antibodies, next generation proteasome inhibitors, epigenetic modulation with histone deacetylase inhibitors, and targeting the tumor microenvironment. In this article, the diagnosis, staging, and prognostic stratification of newly diagnosed MM will be reviewed. Clinical data pertaining to the emerging targeted agents will be discussed, and a suggested framework for integration of these new therapeutic options will be provided.